THE ROLE OF FINANCIAL LAW DURING FINANCIAL CRISES AND RESTORATION OF ECONOMIC STABILITY - Andrii Borovyk; Oleksandr Kravchenko; Dmytro Makharynets (Baltic Journal of Economic Studies)
The modern global financial system is a complex dynamic mechanism whose stable functioning is a prerequisite for the development of both national economies and the global economy as a whole. At the same time, the global financial system may not be a safe source of shocks and disturbances. The article aims to deepen the scientific approaches to defining the theoretical foundations of the study of the causes and typology of global financial crises and to formulate a methodological approach to identifying the possibilities of recovery and economic stabilisation through the use of the main regulatory instruments of financial law. Methodology. The study used the following methods: analysis, systematisation and historical method to analyse and periodise financial crises in the transition period from the late twentieth century to the early twenty-first century; comparison, analogy and systematisation to summarise the causes of financial crises; and the logical consequence method to draw conclusions based on the research. The article examines the specifics of financial crises in the global economy and generalises their periodisation. The systemic determinants of global financial crises are considered. The distinctive features of banking and currency crises are characterised. The article proves that financial crises are not random phenomena, they are caused by various factors, among which are speculative transactions, lack of regulation and supervision, and excessive lending. Particular attention is paid to geopolitical factors of financial crises, as one of the most common in recent decades, and the peculiarities of their manifestation. The paper establishes that, despite the cyclical nature of financial crises, their scale and consequences always vary, which requires the development of dynamic tools for crisis management. The study is aimed at identifying patterns and factors that cause financial crises. Attention is paid to the importance of ensuring the security of financial markets for the economic stability of the State, including for ensuring the financial security of the State. The article presents the interpretation of scientists on the importance of ensuring financial security and security of financial markets, the impact of the proper functioning of such markets on ensuring economic stability. Emphasis is placed on the system of financial security, which includes: budgetary, currency, monetary, debt security, insurance market security and stock market security. The publication highlights the importance of the security of the state's financial markets for ensuring the state sovereignty and integrity of the country, as well as a decent standard of living for Ukrainian citizens. Consideration is given to the current threats to the financial markets of Ukraine in the current situation and under martial law. The factors affecting the economic stability and financial security of the state are considered, and measures to ensure the security of financial markets are proposed. The research identifies threats to the financial security of the state, in particular, the following: non-compliance with the rule of law; imperfect public administration in ensuring financial security; ineffective system of control over budget expenditures; ill-considered monetary policy of the state; ineffective tax system; corruption of state bodies and pressure on business; excessive state budget deficit; and growth of the "shadow" economy; rising external debt; outflow of human capital and demographic crisis; mismanagement of foreign loans and financial assistance. Emphasis is placed on the experience of the European Union (EU) in ensuring the security of financial markets and financial security of the State. The conclusions of the paper demonstrate that for the proper functioning of the state's financial activities and the promotion of Ukraine's European integration, even in the current conditions, the security of the state's financial markets and their proper functioning must be ensured at the appropriate level. The results of the study can serve as a basis for developing a system of indicators of the likelihood of financial crises in order to take timely preventive measures aimed at preventing them or reducing the possible negative consequences of their unfolding.